El principio de interculturalidad dentro de la reparación integral en delitos cometidos por adolescentes infractores indígenas - Lizeth Pamela, Saigua Carrasco (2019)
The principle of interculturality is guaranteed in article 1 of the Constitution of the Republic, and it developed in article 24 of the Organic Code of the Judiciary. From the judicial point of view, it obliges all administrators of justice to apply this principle , in other words, observing each of the differences of a cultural nature in which the substantial parts of the process may be immersed, in order to avoid the violation of the cultural diversity of each person during the processing of the trial. Based on the above, it is stated that the present research work is intended to show that there have been legal cases in which the application of the principle of interculturality although it favors teenage offenders from communities, peoples, and nationalities, on the other hand, it leaves the victim unprotected against the committing of new criminal acts against him or her, likewise it does not guarantee mechanisms of integral reparation of the victim that are considered effective when this principle is applied in judicial practice. In order to fulfill the proposed objectives, the quantitative, qualitative research modality was used, that is, the most important characteristics of this principle were analyzed, among other aspects; and, on the other hand, a field investigation was conducted from which relevant data were obtained related to the application of this principle in judicial practice that allowed us to maintain that the judicial application of this principle in certain cases can harm and protect the victims of the crimes committed by teenage offenders who belong to the indigenous sector.